Analysis of Coastal Tourism Development in the East Coast Region of Sumatera Utara Province - Uswatun Hasanah; Rahmad Sembiring; Annisa Ilmi Faried (Cita konsultindo, 2023)
This study aims to describe and analyze needstourists both in infrastructure development, development of hospitality support capacity, as well as the carrying capacity of the community and local government. The research method used in this study uses the mixed method method using scoring analysis. The results of the scoring analysis show that the problems of beach tourism in the East Coast Region are on average almost the same, namely infrastructure development, hospitality support capacity, and local government support capacity. So we need some recommendations. Such as recommendations for developing infrastructure support capacity, namely accelerating repairs and fulfilling tourism support facilities to provide comfort to tourists when traveling, recommendations for developing hospitality support capacity, namely an action plan to assist the implementation of the Sapta Pesona program for the community. Effective institutional management/strengthening from the community, government and private sector to manage tourism (Pokdarwis). And recommendations for developing the supporting capacity of the role of local governmentpreparing regulations to support east coast tourism activities in Sumatera Utara Province